Novel Diagnostic Tools for Identifying Cognitive Impairment in Dogs: Behavior, Biomarkers, and Pathology - Vikartovska, Zuzana; Farbakova, Jana; Smolek, Tomas; Hanes, Jozef; Zilka, Norbert; Hornakova, Lubica; Humenik, Filip; Maloveska, Marcela; Hudakova, Nikola; Cizkova, Dasa (Frontiers in Veterinary Science, 2021)
Canine cognitive dysfunction syndrome (CCDS) is a progressive neurodegenerative disorder in senior dogs which is mainly associated with decreased ability to learn and respond to stimuli. It is commonly under-diagnosed because behavioural changes are often attributed to the natural process of aging. In the present study, we used for the first time a comprehensive approach enabling early diagnosis of canine patients with mild cognitive disorders (MiCI). We included CADES questionnaires, biochemical parameters and biomarkers in blood serum, and correlated them with post-mortem histopathological changes. The CADES questionnaires enabled us to identify MiCI dogs developing changes mainly in domains corresponding to social interaction and spatial orientation, which seems to be crucial for delineating early cognitive disorders. Biochemical analyses in these dogs showed slightly elevated liver enzyme parameters (AST, ALT) and significantly decreased sodium and chloride levels in blood serum. Furthermore, we describe for the first time significant increase of NFL in blood serum of MiCI dogs, compared to normal aging seniors and young controls, but no changes in TAU protein and Aβ42 peptide levels. In canine brains with cognitive impairment amyloid plaques of mainly diffuse and dense types were detected. Furthermore, activated microglia with amoeboid body and dystrophic processes occurred, in some cases with spheroidal and bulbous swellings. On the other hand, no TAU pathology or neurofibrillary tangles were detected. These results suggest that a combination of CADES questionnaire mainly with CNS injury biomarker (NFL) and with biochemical parameters (ALT, AST, Na, Cl) in blood serum may predict CCDS in senior dogs.